Rancang Bangun Modul Praktikum Programmable Logic Controller Berbasis Outseal PLC - Langit, Sekar; Rahardjo, Pratolo; Nugraha, I Putu Elba Duta (Majalah Ilmiah Teknologi Elektro; Vol 22 No 2 (2023): (Juli - Desember) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2023.v22i02.P18, 2024)
In this research, the design of PLC trainer tools and its accessories was carried out to support the making of practicum modules for Programmable Logic Controller + Lab courses by utilizing the Outseal PLC Mega V3 Standard PP board. There are three experimental designs for the practicum module of the Programmable Logic Controller + Lab course, such as running light, water level control, and application of oil to the machine. In general, the design of this practicum module is divided into 3 stages, including system design, hardware design, and software design. Keyword – PLC Trainer; Practicum; Outseal PLC Mega V3 Standard